ANALISIS MEDIA SOSIAL WHATSAPP DAN ETIKA KOMUNIKASI MAHASISWA STKIP TAMAN SISWA BIMA - Faisal; Irawati, Ika; Wahyudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the use of WhatsApp social media and students' understanding of communication ethics at STKIP Taman Siswa Bima in an academic context. This study focuses on digital communication behavior patterns between students and lecturers through the WhatsApp platform, which has now become the primary means of communication in higher education. This study used a qualitative descriptive method with data collection techniques through in-depth interviews with 15 students from various semesters. The results showed that most students use WhatsApp because it is considered practical, efficient, and responsive. However, some of them still lack understanding of the principles of academic communication ethics, such as using polite language, choosing the right time to send messages, and composing messages formally and clearly. These findings reveal a gap between technological convenience and academic communication maturity. This study contributes to educational institutions in designing policies or training in digital communication ethics, thus enabling them to foster professional, ethical, and effective academic interactions in the era of increasingly rapid social media development.